Green Skills Research in South Africa Models, Cases and Methods, 1st edition - Rosenberg, Eureta (Routledge, 2020)
This book proposes transformative, realist methodology for skills research and planning through an analysis of case studies of the changing world of work, new learning pathways and educational system challenges.